2016
DOI: 10.11648/j.ajbio.s.2016040301.12
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Leaf Extracts of <i>Ricinus communis</i> L. (Euphorbiaceace) Against the Third Instar Larvae of <i>Musca domestica</i> L. (Diptera: Muscidae)

Abstract: The housefly, Musca domestica is a ubiquitous insect that has potential to spread wide variety of pathogens to humans and livestock animals leading to diseases and huge economic losses in developing countries. Flies have resisted human attempts to control them since antiquity and the problem of fly resistance to synthetic insecticides had resulted in need to develop biopesticides as an alternative management tool. Plant product are the most promising sources and under extensive trials for their insecticidal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…The toxicity recorded in this study support different previous studies represented toxicity on larvae and adults as well as on fertility of plant origin essential oils against M. domestica (Pavela, 2008;Morey and Khandagle, 2012;Singh and Kaur, 2016;Walia et al, 2017). A previous study using R. communis extract recorded LC50 value of 353.4 ppm after 72 h of exposure to the extract and reported that the extract contained the ribosome inactivating protein ricin (Alvarez Montes de Oca et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The toxicity recorded in this study support different previous studies represented toxicity on larvae and adults as well as on fertility of plant origin essential oils against M. domestica (Pavela, 2008;Morey and Khandagle, 2012;Singh and Kaur, 2016;Walia et al, 2017). A previous study using R. communis extract recorded LC50 value of 353.4 ppm after 72 h of exposure to the extract and reported that the extract contained the ribosome inactivating protein ricin (Alvarez Montes de Oca et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…A previous study using R. communis extract recorded LC50 value of 353.4 ppm after 72 h of exposure to the extract and reported that the extract contained the ribosome inactivating protein ricin (Alvarez Montes de Oca et al, 1996). A study using the chloroform leaves extract of R. communis predict larval and pupal mortality as well as reduction of pupations and non-emergence of adults of M. domestica as regard to the potent insecticidal component of R. communis (ricinine) confirming the effect on the housefly life cycle (Singh and Kaur, 2016) because ricinine has maximum solubility in chloroform (Rao, 1945). The gas chromatographic analysis with mass spectrometry (GC-MS) detected the main constituents of the R. communis essential oil, α-thujone, 1,8-cineole, α-pinene, camphor and camphene (Kadri et al, 2011;Zarai et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An investigation by has demonstrated the potential of castor against the damaging activity of termites on Mangifera indica and Pinus longifolia, reporting significant weight loss in the woods. Furthermore, it has been reported that the various active substances in castor could potentially interfere with the life cycles of many insect pests, including Callosobruchus chinensis (Uspani et al, 2003), Cosmopolites sordidus (Tinzarra et al, 2006), Spodoptera frugiperda (Rossi et al, 2012) and Musca domestica (housefly) Singh and Kaur (2016).…”
Section: Introductionmentioning
confidence: 99%